Ovarian tumor in women of the late childbearing age: how to assess the risk of cancer - Woźniak, Sławomir; Szkodziak, Piotr; Czuczwar, Piotr; Woźniakowska, Ewa; Milart, Paweł; Paszkowski, Maciej; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2013)
In Poland, about 2,500 women die from ovarian cancer every year. Over 80% of new cases are recorded in patients over 50 years of age. Early symptoms of ovarian cancer are often unclear and similar to those observed in other benign ovarian changes. That is why most patients are diagnosed at advanced stages of the disease, therefore ovarian cancer is the fifth leading cause of cancer mortality in women. In the diagnosis of adnexal masses and the differentiation of malignant and benign tumors, the clinical examination, family history, biochemical markers and ultrasound diagnosis are generally used. Developing methods that facilitate identifying women with ovarian cancer may play a significant role in improving the survival of patients. Using a combined evaluation of CA-125 and HE4 levels, the ROMA (Risk of Ovarian Malignancy Algorithm) algorithm was created to estimate the probability of malignant epithelial ovarian cancer. Moreover, new ultrasound-based algorithms have been developed – Simple Rules and Subjective Assessment, which significantly enhanced both the sensitivity and specificity in detecting malignant adnexal masses. The research of IOTA experts showed that about 8% of ovarian tumors are very difficult to differentiate before surgery, even with the use of the latest modern sonographic and biochemical methods.